Arabian nights - Burton, Richard Francis, Sir, 1821-1890 (Collins classics., 2013)
King Shahryar marries, loves, then kills a young woman each night - until he encounters Scheherezade. For one thousand and one nights, he delays her murder as he eagerly awaits her next tale of love, lust, hilarity, or sorrow. Shahrazade saves herself from execution by distracting King Shahriyar with stories.